Making a Life on Mean Welfare : Voices from Multicultural Sydney - Mitchell, Emma (Book collections on Project MUSE., 2023)
Based on ethnographic fieldwork and the author's own experience, this book explores how diverse welfare users navigate the personal and practical hurdles of Australia's social security system.